2018
DOI: 10.1021/acs.est.8b03265
|View full text |Cite
|
Sign up to set email alerts
|

UV-Light-Induced Aggregation of Arsenic and Metal Sulfide Particles in Acidic Wastewater: The Role of Free Radicals

Abstract: The removal of arsenic and metals by sulfide (S(-II)) from acidic wastewater is an efficient method. However, the small sulfide particles formed in such a process make solid-liquid separation difficult, which greatly hinders its application. This study investigated the aggregation behavior of different sulfide particles (AsS, CuS and CdS) under ultraviolet (UV) irradiation. In the dark, the aggregation rate of the arsenic sulfide (AsS) particles was extremely slow. However, under UV irradiation, the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 45 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…A small amount of sulfur crystal (S 8 ) peaks was also found, which was also reported in our previous research [29]. The generation of elemental sulfur should be produced by the reaction of arsenate in the acidic wastewater with hydrogen sulfide [30,31]. Table 2 shows the elemental contents of the ASS and leaching concentrations of heavy metals.…”
Section: Characterization and Chemical Composition Of The Asssupporting
confidence: 78%
See 1 more Smart Citation
“…A small amount of sulfur crystal (S 8 ) peaks was also found, which was also reported in our previous research [29]. The generation of elemental sulfur should be produced by the reaction of arsenate in the acidic wastewater with hydrogen sulfide [30,31]. Table 2 shows the elemental contents of the ASS and leaching concentrations of heavy metals.…”
Section: Characterization and Chemical Composition Of The Asssupporting
confidence: 78%
“…The raw ASSs were mainly amorphous with a few diffraction peaks (Figure 2). Crystalline sulfur (S 8 ) was observed in the raw ASS, which might be attributed to the reaction of H 2 S and AsO 4 3− during the treatment of acidic arsenic bearing wastewater by H 2 S [28,31]. Moreover, for vacuum or air atmosphere, As 2 O 3 species were apparently detected and the intensity of the peaks increased with the increase of temperature.…”
Section: Morphology Change and Phase Transformationmentioning
confidence: 99%
“…33,34 Such photoactive properties have promised that the environmental behaviors of MoS 2 including aggregation are susceptible to illumination. Numerous studies have reported that light irradiation can alter aggregation behaviors of nanomaterials by initiating redox reactions (As 2 S 3 ), 35 removing surface groups or coatings (carbon nanotubes, 36,37 GO, 38 TiO 2 39 ), or inducing surface plasmon oscillation (Ag, Au). 40−42 For MoS 2 , long-term light exposure can reduce the surface charge through redox reactions and thus destabilize the nanosheet.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the 2H-MoS 2 phase, supra-band-gap illumination allows electron–hole separation, which can drive photochemical reactions. , Compared to the 2H phase, the metastable, metallic 1T phase possess a higher concentration of free charge carriers, and with sufficient Li or K doping can achieve surface plasmon resonance under visible and near UV range. , Such photoactive properties have promised that the environmental behaviors of MoS 2 including aggregation are susceptible to illumination. Numerous studies have reported that light irradiation can alter aggregation behaviors of nanomaterials by initiating redox reactions (As 2 S 3 ), removing surface groups or coatings (carbon nanotubes, , GO, TiO 2 ), or inducing surface plasmon oscillation (Ag, Au). For MoS 2 , long-term light exposure can reduce the surface charge through redox reactions and thus destabilize the nanosheet . Until now, however, the effect of light irradiation on the initial aggregation of pristine MoS 2 nanosheets remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Stokes formula, which shows that the settling rate of a particle is proportional to the particle size, increasing the particle size of metal sulfides is an essential way to increase their settling performance. 20 Previous studies tried to increase the size of particles by increasing the dosing point and circulating the flow rate to reduce solution supersaturation. Due to the difficulty of controlling the local supersaturation of sulfides, there is still a large amount of fine particle formation.…”
Section: Introductionmentioning
confidence: 99%